Rhinolophus sinicus virome revealed multiple novel mosquito-borne zoonotic viruses - Peng, Chengcheng; Zhang, Duo; Li, Chenghui; Li, Yiquan; Zhang, He; Li, Nan; Xiao, Pengpeng (Frontiers in Cellular and Infection Microbiology, 2022)
To exploit the Rhinolophus sinicus–specific virome, 29 Rhinolophus sinicus were gathered in Lincang, China. Enriched viral sequences of 22 virus families were acquired by metavirome techniques. Hereby, the part of virome in Rhinolophus sinicus, including Chikungunya virus (CHIKV), Getah virus, and Japanese encephalitis virus (JEV) were validated by PCR. Five CHIKV viral sequences were amplified, among which CHIKV-China/B2016C-1 shared the highest homology to CHIKV isolated from Italy in 2007, with the genotype as African ECS. Eight JEV viral sequences were amplified, of which JEV-China/B2016E-1 shared the highest homology with at least 91.3% nt identity with the JEV sequence found in South Korea in 1988 and was classified as genotype III. Notably, JEV was isolated for the first time in Rhinolophus sinicus. The newly isolated JEV-China/B2016-1 could increase infectivity while passaging in Vero cells from BHK-21 cells. Overall, the research sheds insight into the diversity and viral susceptibility dynamics of the virome in Rhinolophus sinicus and reveals new light on the ecology of other important viral hosts.